Sharing economy: drivers and barriers to portuguese travelers use peer-to-peer accommodation rentals - Barbosa, Cláudia Patrícia Rodrigues (2017)
Sharing economy has disrupted some traditional business models most precisely tourism and hospitality. Enabled by technological advances, economic and social changes, this growing movement is changing the way we consume. Over the past couple of years’, startups have flourished and showed to the industry that the future in this business is uncertain. These startups are empowering individuals to distribute and share access to excess capacity of accommodation. Examples of such companies are Airbnb, HomeAway, FlipKey (acquired by TripAdvisor in 2008), Tripping.com, VRBO, HouseTrip, VayStays, VaycayHero, Roomorama, 9flats, Travelmob, HomeEscape or Wimdu. For instance, Airbnb nowadays allows people to have an accommodation at 2,3 million room inventory (Skift, 2016b) spread in more than 65.000 cities in 191 countries (Airbnb, 2017a). On other hand, we have Marriott International, the world's largest hotel chain, with 6.000 properties in 122 countries and 31.000 room inventory (Marriott, 2017). So, Airbnb’s room inventory makes it bigger than the three largest hotel chains - Hilton, Marriott, and InterContinental - combined (Bloomberg, 2017). This digital disruption poses a huge question to the business: are these platforms creating a new market or replacing the existing one? Due to the rise of businesses using the sharing economy concept, it is important to understand why consumers are adopting so enthusiastically these kinds of services. What are the main reasons that drive or hinder travelers from engaging in P2P accommodation rentals? The present dissertation will explore sharing economy, especially in tourism and hospitality, and focus on what are the drivers that lead Portuguese travelers using P2P accommodation rentals.